Rumpelstiltsken’s feat: cloth and German trade with Iceland (AmS-Skrifter, 2020)
Identifying foreign cloth imports in the Icelandic archaeological corpus is difficult at best, yet given widespread similarities in homespun cloth from sites across the country, imported cloth can be identified visually through the presence of refined finishing techniques (such as teaseling, shearing, and fulling) that were uncommon in Iceland and were the products of specialist craftsmen in Europe. This paper examines textile assemblages from deposits datable to the period of Hanseatic trade at three sites, Gilsbakki, Reykholt, and Stóra-Borg that represent two wealthy, interior, parish centres and a moderate-sized coastal farm, respectively. Variations in the number and diversity of imported cloth items within these sites’ assemblages suggest that while Hanseatic material culture was widely spread on Icelandic rural sites, the nature of the material culture sub-assemblages attributable to Hanseatic trade was not obviously a direct function of households’ wealth or proximity to harbours but may have engaged other cultural factors linked to the political and social challenges of the post-Reformation period and the roles of individual households in regional or intra-Icelandic trade.